Evaluasi Pelaksanaan Program Kampung Keluarga Berkualitas Di Desa Busung Kecamatan Seri Kuala Lobam Kabupaten Bintan - Aulia Nurbalqis; Jamhur Poti; Rudi Subiyakto (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
In Bintan Regency, there are already 18 KB (Keluarga Berkualitas) villages spread across 10 sub-districts. One of them is Seri Kuala Lobam KB Village, it’s located in Busung village. This study aimed to evaluate the implementation of the Quality Family (KB) Village Program in Busung Village, Seri Kuala Lobam District, Bintan Regency. In this research, the theory used is Dunn's (2003) policy evaluation theory. The research used descriptive qualitative as the method. Data collection techniques are carried out by observation, interviews, and documentation. The data analysis technique used was by reducing data, presenting data and drawing conclusions. The research results were, Indicators of effectiveness have not been effective, due to the lack of understanding of the community in Busung Village about Quality Family Villages. Efficiency indicators were not yet efficient, due to the lack of participation of the comunity and constraints in managing time. Facilities and infrastructure indicators were also inadequate like there is not any town hall meeting available. Indicators of equalization, was not yet evenly distributed throughout society. Indicators of responsiveness, got support from the community. Accuracy indicator, it was right on target but was not comprehensive in all circles of society.